Courses on speech prosody - Meireles, Alexsandro (Cambridge Scholars Publishing, 2015)
In recent years, speech prosody research in Brazil has grown significantly, mainly due to a series of events organized through the support of the Brazilian government. The two most important of these events are the biennial Brazilian Colloquium on Speech Prosody and School of Prosody, both of which attract a number of prominent Brazilian and international researchers. Due to the success of the 1st Brazilian Colloquium on Speech Prosody, the Luso-Brazilian Association of Speech Sciences (LBASS) was created in 2007 to support the organization of the Speech Prosody 2008 Conference, which was held.